دور الضمانات في تطور المصارف الاسلامية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Islamic banking refers to a system of banking or banking activity that is consistent with the principles of the Shari'ah (Islamic rulings) and its practical application through the development of Islamic economics. The principles which emphasise moral and ethical values in all dealings have wide universal appeal. Shari'ah prohibits the payment or acceptance of interest charges (riba) for the lending and accepting of money, as well as carrying out trade and other activities that provide goods or services considered contrary to its principles. While these principles were used as the basis for a flourishing economy in earlier times, it is only in the late 20th century that a number of Islamic banks were formed to provide an alternative basis to Muslims although Islamic banking is not restricted to Muslims .The origin of the modern Islamic bank can be traced back to the very birth of Islam when the Prophet himself acted as an agent for his wife's trading operations. Islamic partnerships (mudarabah) dominated the business world for centuries and the concept of interest found very little application in day-to-day transactions. . Such partnerships performed an important economic function. They combined the three most important factors of production, namely: capital, labour and entrepreneurship, the latter two functions usually combined in one person. The capital-owner contributed the money and the partner managed the business. Each shared in a pre-determined share of the profits. If there was a loss, the capital-provider lost his money and the manager lost his time and labour.